Public relations - Smith, Ron (New York Routledge, 2014)
Public Relations: The Basics is a highly readable introduction to one of the most exciting and fast-paced media industries. Both the practice and profession of public relations are explored and the focus is on those issues which will be most relevant to those new to the field: The four key phases of public relations campaigns: research, strategy, tactics and evaluation. History and evolution of public relations. Basic concepts of the profession: ethics, professionalism and theoretical underpinnings. Contemporary international case studies are woven throughout the text ensuring that the book is relevant to a global audience. It also features a glossary and an appendix on first steps towards a career in public relations making this the book the ideal starting point for anyone new to the study of public relations.
Keywords: Public relations